Ethics and end-of-life in pediatric and neonatal ICUs: a systematic review of recommendations - Diana Špoljar; Sunčana Janković; Dina Vrkić; Geraldine McNamara; Marko Ćurković; Milivoj Novak; Boris Filipović-Grčić; Stefan Grosek; Chris Gastmans; Bert Gordijn; Ana Borovečki (BMC Palliative Care)
Abstract Background Working in neonatal intensive care units (NICUs) or pediatric intensive care units (PICUs) entails making difficult decisions about children at the end of their lives that raise significant ethical issues. This review identified the ethical content of the papers containing expert guidelines and recommendations in relation to end-of-life decision-making in NICUs and PICUs, by analyzing ethical positions and ethical principles behind them. Methods Systematic search was limited to the period from 1990 to 2023 and encompassed 6 bibliographic databases (Medline, PubMed, CINAHL, APA PsycINFO, Web of Science Core Collection, and Scopus), grey literature sources and relevant reference lists. The international, national, or institutional papers providing expert guidelines and recommendations comprehensively addressing either withholding/withdrawing of life sustaining treatment, palliative care, and/or intentional life terminating actions in NICUs and PICUs were included in analysis. Also, only papers published in English language were considered. Papers that were not developed by intensive care expert communities and those that were either too narrow (e.g., dealing with specific issues or specific patient groups) or broad (e.g., addressing issues of interest on general and abstract level) were excluded. The search data were gathered and deduplicated, partly by Mendeley software. Titles and abstracts were screened by three independent reviewers, and full-text papers further reviewed and assessed for eligibility. Subsequently, data of interest were extracted, and qualitative analysis was performed. Results Initial search retrieved 6784 papers from bibliographic databases and 363 from other utilized sources. Titles and abstracts from 2827 papers were screened. 17 full texts were further assessed resulting in a total number of 9 papers (6 from bibliographic databases and 3 from other sources) which met the inclusion criteria and were included for analysis. The papers were published from 2001 to 2021. Four papers primarily focus on NICU setting, while five on PICU. A total of 38 ethical positions were identified and were grouped under 5 themes according to the content of the positions, relating to: patients, parents, medical team, decision-making and treatment options. A total of 12 ethical principles were mentioned in the papers. The principle of beneficence emerged as the most prominent one. It was explicitly mentioned in all included papers except one. Conclusions This review has shown that papers containing guidelines and recommendations on end-of-life decision-making in the NICU and PICU promote similar stances. The ethical principle of beneficence is at the core of the decision-making process, and all decisions are made focusing on the child’s best interests.